PERLINDUNGAN HUKUM TERHADAP PEMEGANG SERTIPIKAT HGB UNTUK MEMPERPANJANG DAN MEMPERBARUI HGB DI ATAS HAK PENGELOLAAN STUDI PUTUSAN MA NO 3090/K/Pdt/2017 - Hasni .; Steven Ouddy (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2019)
This research is about legal protection for holders of certificate of building use rights to extend and renew building use rights over management rights which is the main problem is how the authority of holders of certificates of building rights in extending and renewing building rights over management rights and how to protect them against Building Rights holders who have expired brut sktill occupy q lanqd and builqdings. The metqhod ursed in theis stusdy is normative law, namely research that seeks to connect between legal norms that apply to the reality that exists in society. The soqurce of legal matqerial used is primarqy legqal matqerial and secoqndary legal matuerial. The research specifications used are analytical descriptive which are expected to be able to givqe a detaqiled, systeqmatic, andcomprehensive description of gall mattersrelating to Management Rights, Building Use Rights and legal protection against Rights holders to Build on Management Rights. The conclusion of this paper is that Building Use Rights over Management rights can be extended based on the applicable Law and good faith